2
$\begingroup$

Let $\Gamma$ be the Gamma function and abbreviate $x!:=\Gamma(x+1)$, $x>-1$. For $\alpha>0$ let us generalize the binomial coefficients in the following way: $$\binom{n+m}{n}_\alpha:=\frac{(\alpha n+\alpha m)!}{(\alpha n)!(\alpha m)!}$$

Of course for $\alpha=1$ this reduces to the ordinary binomial coefficients. My question is:

How can one show that this is really the only case where they coincide?

That is, $\displaystyle\binom{n+m}{n}=\binom{n+m}{n}_\alpha$ for all $n,m\in\mathbb{N}$ implies $\alpha=1$.

Or even more general (but currently not of interest to me):

$\displaystyle\binom{n+m}{n}_\alpha=\binom{n+m}{n}_\beta$ implies $\alpha=\beta$.

I tried to use Stirling's formula: $\Gamma(z+1)\sim\sqrt{2\pi z}\bigl(\frac{z}{e}\bigr)^z$ as $z\to\infty$, but didn't get very far.

Thanks in advance for any help.

$\endgroup$
0
$\begingroup$

Set, for example, $m=1$ and consider the limit $n\rightarrow\infty$. Then $$ {\alpha n+\alpha\choose \alpha n}\sim \frac{(\alpha n)^{\alpha}}{\alpha!},\qquad {n+1 \choose n}\sim n.$$ It is clear that the only possibility for both asymptotics to agree is $\alpha=1$. In the more general situation, the same argument shows that $\alpha=\beta$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.